The Main Character’s Internal Conflict in The Split Movie (2017): Internal Conflict - Asrullah, Asrullah; Nasrum, Nasrum; Taufik, Muhammad; Syukur, Helmi (Journal of Islamic Culture and Literature (JICeL), 2024)
This study aims to analyze “The Split" movie by using Roman Jakobson's structuralism approach, with Myers' conflict theory. This approach is used to find out the internal conflicts that occur in the main character in the split film and the conflict resolution. Besides that, the researcher elaborated on the results of this study using a qualitative descriptive method. As a result, the researchers found five conflicts within the main character in the film "Split", the five conflicts include: Personality Battles, emotional control, Value and Motivational Conflicts, Sense of Identity and Past Influences. Meanwhile, the researchers also found conflicts between the main figures and the community, including: conflicts with investigators and psychiatrists, conflicts with the victims, namely the three students, and conflicts with employees and security guards. Finally, the researcher found a solution to the conflict that occurred in the split film, namely: Psychological Therapy, Personality Integration, Awareness and Acceptance and Social Support. Therefore, if someone experiences internal conflicts or mental problems, it is very important to seek professional help such as a psychologist or psychiatrist who can provide appropriate and supportive treatment. Keywords: Internal Conflik, Literary Work, Movie